2019
DOI: 10.13181/mji.v28i3.2690
|View full text |Cite
|
Sign up to set email alerts
|

A glance at molecular mechanisms underlying cisplatin-induced nephrotoxicity and possible renoprotective strategies: a narrative review

Abstract: Cisplatin is a platinum-based drug that is usually used for the treatment of many carcinomas. However, it comes with several devastating side effects, including nephrotoxicity. Cisplatin toxicity is a very complex process, which is exacerbated by the accumulation of cisplatin in renal tubular cells via passive diffusion and transporter-mediated processes. Once cisplatin enters these cells, it induces the formation of reactive oxygen species that cause cellular damage, including DNA damage, inflammation, and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…30 In addition to CTRs, organic cation transporter 2 (OCT2) is the primary transport protein mediating the cellular uptake of CDDP and regulating the cellular uptake of cationic species. 31 A recent study showed that CDDP does not cross-react with other OCT protein family members, 32 which may explain why CDDP is kidney-specific. Among the efflux transporters, MATE1 is an organic cationic reverse transporter that is responsible for the outflow of CDDP from epithelial cells to urine.…”
Section: Nephrotoxicity Mechanisms Of Cddp-based Chemotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…30 In addition to CTRs, organic cation transporter 2 (OCT2) is the primary transport protein mediating the cellular uptake of CDDP and regulating the cellular uptake of cationic species. 31 A recent study showed that CDDP does not cross-react with other OCT protein family members, 32 which may explain why CDDP is kidney-specific. Among the efflux transporters, MATE1 is an organic cationic reverse transporter that is responsible for the outflow of CDDP from epithelial cells to urine.…”
Section: Nephrotoxicity Mechanisms Of Cddp-based Chemotherapymentioning
confidence: 99%
“…For example, a low concentration of CDDP causes apoptosis where necrosis occurs with high concentration treatment. 3 Apoptosis induced by CDDP administration can occur through the intrinsic (mitochondrial) pathway or via ER stress, 42 the signaling pathways involved in CDDP-induced apoptosis in PTECs are shown in Fig. 2b.…”
Section: Mechanisms Of Cell Death In Cddp-induced Nephrotoxicitymentioning
confidence: 99%